Do Government Revenues Matter for Economic Growth? Evidence from Nigeria - Isiaka Akande Raifu; Abiodun Najeem Raheem (European Journal of Government and Economics (EJGE), 2018)
The bursting of crude oil prices in the international market since mid-2014 has resulted in dwindling oil revenue, which has led to economic recession in Nigeria. The recession has further exacerbated existing socioeconomic problems bedeviling the country. In the light of this, we examined the effect of government revenues (oil and (Non-oil revenues) on economic growth, both in the short-run and the long-run using autoregressive distributed lag method. Our findings show that government revenues are indispensable to economic growth in Nigeria. In addition, we found that economic growth is more responsive to oil revenue than (Non-oil revenue. Based on our findings, we advocate for effective and efficient use of government revenues. Furthermore, since oil revenue fluctuates more than (Non-oil revenue, we further advocate for creation of an enabling business environment geared towards improving the contribution of the (Non-oil sector to the government revenue base.
Keywords: 330; Oil Revenues; Non-oil Revenues; Economic Growth; ARDL